Resim İş Eğitimi dersinde dışavurumcu çalışmaların 6-7 ve 8. sınıf öğrencilerinin yaratıcılıklarına olan etkisi - Erinç, Ceyda (My University, 2004)
Hazırlanan bu tez çalışması; dışavurumcu sanat hareketinin ışığı altında, ilköğretim ikinci kademe resim iş dersi programında, alternatif uygulamalar önermeyi amaçlamaktadır. Çalışmada öncelikli olarak Dışavurumcu üslup ve sanatçılarla ilgili bilgi verilmiş; Dışavurumcu üslubun sanat eğitimi programında ve öğretimde değerlendirilmesi gereken yönleri açıklanmaya çalışılmıştır. Bu noktada çocukların resim gelişim evreleri incelenerek, ilköğretim ikinci kademe öğrencilerinin yaş dönemleri ve psikolojik yapıları araştırılmıştır. Bu yaş dönemi öğrencilerine yaptırılan uygulamalara yer verilerek, ilköğretim 6 - 7 ve 8. Sınıf resim iş dersi müfredat lantı kurulmuştur. Yaş dönemleri itibari ile duyguların yoğun ve karmaşık bir şekilde yaşandığı ergenlik döneminde olan 6 - 7 ve 8. Sınıf öğrencilerine uygulatılacak sanat eğitimi programının, onları kısıtlamadan yaratıcılıklarını arttırıcı nitelikte olması gerekmektedir. Name and Surname: Ceyda Erinç Field: Department of Art, Section of Painting Programme: Painting-Handicrafts Teaching Supervisor: Doç. Dr. Ümran Bulut Degree Awarded and Date: Master - July 2004 Expressionism and expressionist applications

This thesis aims to propose alternative applications in the program of second grade painting/ handicraft courses in primary schools. In the study, information was given about expressionism and expressionists and aspects to be considered during education were described. At this point, the painting development phases of children are researched and age periods and psychological structures of second grade primary school students are mentioned. Applications performed by students of the related age period are examined and the syllabus of painting courses for 6th, 7th and 8th classes primary school students is examined. As per their age period, the art education program for 6th, 7th and 8th class students should be able to increase their creativity without limiting them, as the students in the puberty period have intense and complex sentiments. In an art education program targeting to develop the creative power of each student, adding expressionist applications to the program would contribute to the development of artistic and creative thoughts. At this point the attitude of the art teacher to the students and her/ his way to assess students' painting works is very important. This thesis aims to serve as a guide for educators in performing expressionist applications is 6th, 7th and 8th classes in primary schools.
Keywords: Eğitim, Resim